Gestión de la cadena de abastecimiento del biodiésel: una revisión de la literatura - Barón, Manuel; Huertas, Isaac; Orjuela Castro, Javier Arturo (Ingeniería, 2013)
The benefi ts of biofuels have been refl ected in an increasing number of countries that are introducing (or planning to introduce) policies to increase the proportion of biofuels in their energy mix. Currently, only small quantities of biofuels are traded on international markets because most of these fuels are consumed domestically. However, a rapid expansion of bio-fuel trade is expected since many countries have no domestic capacity to supply their own demand. Based on the expected-growth trend of the bio-fuels business, both globally and locally, it seems appropriate to have the technical tools to support decision making in agribusiness management so as to make better use of a so-far nascent market; yet knowing that in the medium and long term, such a market may become a large manufacturing sector that brings development to its productive regions. This paper attempts to present a comprehensive survey of the bio-diesel supply chain together with mathematical models intended to support decision-making in supply chain management.